2022
DOI: 10.1186/s42155-022-00306-1
|View full text |Cite
|
Sign up to set email alerts
|

One year clinical outcomes of Rutherford 6 chronic limb threatening ischemia patients undergoing lower limb endovascular revascularisation from Singapore

Abstract: Background Percutaneous transluminal angioplasty (PTA) is widely used as a first-line revascularisation option in patients with chronic limb threatening ischemia (CLTI). This study aimed to evaluate the short-term endovascular revascularisation treatment outcomes of a cohort of Rutherford 6 (R6) CLTI patients, from a multi-ethnic Asian population in Singapore. Patients with R6 CLTI who underwent endovascular revascularisation from June 2019 to February 2020 at Singapore General … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…We tested with logistic regression the preprocedural characteristic parameters and procedural approach to determine independent predictors of target vessel restenosis. (8). A comprehensive meta-analysis published in 2019 revealed that smoking, hypertension, and hypercholesterolemia, in addition to diabetes, are major risk factors for PAD.…”
Section: Independent Predictors Of Target Vessel Restenosismentioning
confidence: 99%
“…We tested with logistic regression the preprocedural characteristic parameters and procedural approach to determine independent predictors of target vessel restenosis. (8). A comprehensive meta-analysis published in 2019 revealed that smoking, hypertension, and hypercholesterolemia, in addition to diabetes, are major risk factors for PAD.…”
Section: Independent Predictors Of Target Vessel Restenosismentioning
confidence: 99%